Biocontrol potential of plant growth-promoting rhizobacteria (PGPR) against Sclerotiorum rolfsii diseases on sugar beet (Beta vulgaris L.). (May 2022) - Farhaoui, Abdelaaziz; Adadi, Asmae; Tahiri, Abdessalem; El Alami, Nabila; Khayi, Slimane; Mentag, Rachid; Ezrari, Said; Radouane, Nabil; Mokrini, Fouad; Belabess, Zineb; Lahlali, Rachid
Abstract: A total of 49 bacterial isolates were collected from the sugar beet rhizosphere in two regions of Morocco (Kenitra and Meknes). These bacteria were tested for their inhibitory activity against Sclerotium rolfsii Sacc ., the causative pathogen of damping-off and root rot of sugar beet. Ten isolates showed a high ability to inhibit the mycelial growth of the pathogenic fungus in dual culture bioassays. The molecular identification based on 16S ribosomal DNA gene revealed that these isolates belong to the Bacillus genus. In addition, these bacterial isolates have also been characterized in terms of the production of certain antifungal products as well as for their capacities as plant growth-promoting traits. Under greenhouse conditions, sugar beet seeds treated with the each bacterium showed significant reduction in damping-off disease. Plants from treated seeds showed significant increases in both the length of shoots and roots, and the plant fresh and dry weight. Iinterestingly, these selected bacterial isolates displayed high antagonistic activity against S. rolfsii, and significantly reduced the severity and incidence of root rot disease. Therefore, these results highlighted that the soil harbors antagonistic bacteria offering several plant growth-promoting (PGP) traits, which can be exploited as a powerful growth promoter and/or biological control agent in sugar beet plants. Highlights: In vitro, ten tested bacterial isolates displayed high inhibition rate of the mycelial growth of S. rolfsii (greater than 50%). Bacteria evaluated showed their capacity to produce extracellular enzymes (PGPR effect) and antibiotic metabolites belonging to the lipopeptide family. Under greenhouse conditions, sugar beet seeds treated with each bacterium showed significant reduction in damping-off disease caused by S. Rolfsii. Plants grown from seeds treated with each bacterium tested showed a significant increase in plant growth parameters. Selected bacterial isolates significantly reduced the severity and incidence of root rot in sugar beet and B. halotolerans strain MW644679 was most important in controlling root rot caused by S. rolfsii.